Upfront Surgery vs. Primary Chemoradiation in an Unselected, Bicentric Patient Cohort with Oropharyngeal Squamous Cell Carcinoma—A Matched-Pair Analysis - Philipp H. Zimmermann (MDPI AG, 2021)
The two pillars of therapy for oropharyngeal squamous cell carcinoma (OPSCC) are upfront surgery and primary chemoradiotherapy. Substantial regional preferences exist with regard to the selection of treatment. Despite new therapeutic approaches, patient survival remains poor, with an approximate overall survival (OS) rate of 50% at five years. This study was conducted to investigate a potential survival benefit depending on the treatment modality in OPSCC patients. We retrospectively collected data of 853 patients with histologically confirmed OPSCC from the Giessen and Maastricht cancer databases. To identify risk factors affecting survival, a Cox-proportional hazard model was applied to 442 patients with complete data sets. Based on this cohort a matched-pair analysis with 158 patients was performed to compare OS rates of patients treated either with upfront surgery or primary chemoradiation. For the collective cohort, patients treated with upfront surgery had significantly improved OS rates compared to patients treated with primary chemoradiation. In the matched-pair analysis adjusted for patients’ T-, N- and HPV-status as well as risk profile, we observed that both treatment approaches offered equivalent OS rates. Our study emphasizes that treatment recommendations should be made whenever possible on the basis of side-effect profiles caused by the therapeutic approach used. To draw further conclusions, results of the ongoing “best of” (NCT2984410) study are eagerly awaited, investigating the functional outcome after treatment of OPSCC patients.